Effect of mixing urea with humic acid and acid sulphate soil on ammonia loss, exchangeable ammonium and available nitrate - Mohd Yusuff, Mohd Taufik; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Science Publications, 2009)
Problem statement: Ammonia loss due to rapid hydrolysis of urea in soil following surface application can be substantial. Ammonia loss in agriculture is estimated to be 1 to 60%. This laboratory study compared the effect of three different urea-humic acid-acid sulphate soil mixtures on NH3 loss and soil ammonium and nitrate contents, with loss from surface applied urea without additives (urea alone). Approach: Humic acid, acid sulfate soil and soil use in the incubation study was analyzed for selected soil physical-chemical properties. The fertilizers mixture and ammonia loss was done using standard methods. The treatments were evaluated in Randomized Complete block Design with 3 replications. The data obtained at the end of the study on total ammonia loss, soil pH, exchangeable ammonium and available nitrate were analyzed using analysis of variance and the means were compared using Duncan’s test using Statistical Analysis System (SAS) version 9.2. Results: The soil used to test treatments was a sandy clay loam Typic Paleudults (Nyalau series). The mixture significantly reduced NH3 loss by between 31.5 and 36.7% compare with urea alone with larger reductions with higher rate of humic acid (0.75 and 1 g Kg-1 of soil) and acid sulphate soil (0.75 g Kg-1 of soil). The impact of the treatment also showed significant effect on the soil pH and ammonium content at the end of study. Conclusion: Amending urea with acid sulphate soil and humic acid can reduce ammonia loss in acid soils by improving ammonium retention. This may in effect improve urea-N use efficiency as well as reducing environmental pollution in agriculture.